Mirtazapine in Comorbid Major Depression and Alcohol Dependence: An Open-Label Trial - Cornelius, Jack R. (2012)
OBJECTIVE: This was a first pilot study evaluating the acute phase (8-week) efficacy of the antidepressant medication mirtazapine for the treatment of depressive symptoms and drinking of subjects with comorbid major depressive disorder and alcohol dependence (MDD/AD). We hypothesized that mirtazapine would demonstrate within-group efficacy for the treatment of both depressive symptoms and drinking in these subjects. METHODS: We conducted a first open label study of the second generation antidepressant mirtazapine in 12 adult outpatient subjects with comorbid major depressive disorder/alcohol dependence. The pharmacological profile of that medication is unique among antidepressants, unrelated to tricyclics or selective serotonin reuptake inhibitors. RESULTS: Mirtazapine was well tolerated in this treatment population. Self-reported depressive symptoms decreased from 31.8 to 8.3 on the Beck Depression Inventory, a 74.0% decrease (p<0.001), and drinking decreased from 33.9 to 13.3 drinks per week, a 60.8% decrease (p<0.05). None of the subjects were employed full-time at baseline, but 9 of the 12 (75%) were employed full-time at end-of-study. CONCLUSIONS: These preliminary findings suggest efficacy for mirtazapine for treating both the depressive symptoms and excessive alcohol use of comorbid major depressive disorder and alcohol dependence. Double-blind studies are warranted to further clarify the efficacy of mirtazapine in this population.